Influence of step faceting on the enantiospecific decomposition of aspartic acid on chiral Cu surfaces vicinal to Cu{111}. Issue 75 (26th August 2016) - Reinicker, A. D.; Therrien, A. J.; Lawton, T. J.; Ali, R.; Sykes, E. C. H.; Gellman, A. J.
Abstract : The crystallographic orientation of chiral step facets created byl -aspartic acid adsorption dictates enantioselectivity on chiral surfaces vicinal to Cu{111}. Abstract : On surfaces vicinal to Cu{111}, l -aspartic acid (l -Asp) adsorption causes steps to facet enantiospecifically into {310} R and {320} S steps.l -Asp has its highest heat of adsortion on surfaces that naturally expose the {310} R or {320} S steps but decomposes preferentially on the {310} R steps.